Less Is More: Surgical Procedure Time and Risk of Infections, Length-of-Stay, and Readmission across Three Distinct Surgeries - Parikh, Ronak (Open Forum Infect Dis, 2017)
BACKGROUND: Longer surgical total procedure times (TPT) have been associated with increased postoperative complications. It is unclear what the effect of TPT is on length-of-stay (LOS) or 30-day readmission rate (RAR). METHODS: We performed a retrospective study of patients undergoing knee arthroplasty (KA), colectomy, and craniectomy at NorthShore University HealthSystem from 1/2007 to 12/2013. Clinical data were extracted from the Data Warehouse and charts were reviewed. We standardized surgery times for each procedure and categorized into two groups: times <75‰ (short procedures) vs. times >75‰ (long procedures). We used χ (2) and t-test to compare categorical and continuous variables. We performed multivariate logistic regression for predictors of surgical site infection (SSI). RESULTS: In univariate analyses, long procedures were associated with higher incidence of fevers, SSI, longer LOS, and 30-day RAR (Table 1). TPT was not associated with other postoperative complications. TPT remained an independent predictor of SSI in multivariate (MV) analysis (Table 2). CONCLUSION: High TPT was associated with increased SSI, LOS, and 30-day RAR. Understanding variation in TPT may help decrease SSI and healthcare utilization. DISCLOSURES: All authors: No reported disclosures.